If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3 + 4x) + -3 = 42 (3 * 3 + 4x * 3) + -3 = 42 (9 + 12x) + -3 = 42 Reorder the terms: 9 + -3 + 12x = 42 Combine like terms: 9 + -3 = 6 6 + 12x = 42 Solving 6 + 12x = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 12x = 42 + -6 Combine like terms: 6 + -6 = 0 0 + 12x = 42 + -6 12x = 42 + -6 Combine like terms: 42 + -6 = 36 12x = 36 Divide each side by '12'. x = 3 Simplifying x = 3
| -8x-3=10+3x | | 5x^2+7x=0 | | 12x^2+7x+1=0 | | 9x-2+21=10-7 | | -y=x | | -56x^2-12x+8=0 | | -y=0.2x+6 | | 8x^2+2=8x^2 | | 30x^2+40x+10=0 | | 51-2x=16x+19 | | 0.5y=7x-1 | | 18x-8=10x+4 | | y=0.3x | | 8+9x=-3 | | 11-8x=79-36x | | 11x^2+21x+10=0 | | 2a^2+11a+5=0 | | y=-0.75x-3 | | 8-2x+9=11 | | 56x^2-77x+21=0 | | a-3/4= | | 3x+4-2=5-3 | | 16x^2-36x+8=0 | | 10x^2+9x=-2 | | 10x+2=9x+21 | | 0=6x^2-11x+4 | | 0=6x^2-11+4 | | 0.2x-0.3y=0.14 | | m+5=m(-3) | | 16r^2-9=0 | | 2x^2+10x-20=0 | | -90=ac |